Theories and frameworks in second language processing. Issue 4 (18th October 2016) - MALKO, ANTON; EHRENHOFER, LARA; PHILLIPS, COLIN
Abstract : Analyzing L2 sentence processing in terms of cue-based memory retrieval is promising. But this useful general framework has yet to become a specific theory of L1-L2 differences.